Cultural influences in self-directed learning among malay adult learners - Ahmad, Badli Esham; Abdul Majid, Faizah (2011)
More adults are pursuing higher education and self-directed learning (SDL) is essential in adult learning (Hsu and Shiue, 2005). SDL inculcates the idea of independent, take control of one's own learning determination and life-long learning (Guglielmino, 2006). Culture is important in learning (Lal 2003) and it influences the learners' learning styles (Manikutty, Anuradha and Hansen, 2007). The Malays are considered as hierarchical, collective, relationship oriented and masculine in nature with a strong influence of Islam (Asma 2006). Study on the influence of cultural orientations on SDL has been minimal (Hudson & Ramamoorthy, 2009), particularly on the Malay adult learners. Ahmad Badli Esham and Faizah (2010) found that the Malay cultural values have a mixed influence on the SDL readiness of the Malay adult learners. Thus, the paper intends to look in more depth at the relationship between SDL readiness and the Malay cultural values. It seeks to identify the level of SDL readiness of the Malay adult learners. Secondly, the paper looks into the cultural dimensions of the Malays (Hofstede, 1980) and finally it describes the correlation between the Malay cultural dimensions and SDL. Two sets of questionnaires were distributed to one hundred adult learners taking bachelor's degrees in distance learning mode. The first questionnaire, Self-directed Learning Readiness Survey (SDLRS) (Guglielmino, 1977), is used to measure the level of SDL readiness. The second set, Value Survey Module (VSM 94) (Hofstede, 1994), is to determine the cultural dimension scores of the group. The VSM 94 scores were then compared to the scores obtained by Hofstede (1980). Next, both SDLRS and VSM 94 scores were correlated to determine any significant relationships between SDL readiness and Malay cultural dimensions. The study found that the Malay adult learners have an average level of SDL readiness. The cultural dimensions of the Malays are in contrast to the contemporary understanding of Malay cultural dimensions. The learners are masculine and more oriented to individualism, less collectivist and hierarchical in nature and have a high long term orientation. In addition, these traits are similar to the characteristics of a self-directed learner. However, statistically, cultural dimensions have very low correlation with SDL readiness. Culture does not seem to have a strong influence on SDL readiness despite the contrasting findings of the Malay cultural dimensions. Even though without any positive relationship between culture and SDL, the findings on cultural dimensions would be able help educators to plan, structure course designs and learning support systems that focuses on the cultural dimensions of the learners. In lieu of the future of education, developing SDL readiness among the Malay adult learners and enhancing the learner support system would help to enhance their learning experience.